SP9.2.1 Postoperative outcomes in patients undergoing Total Pelvic Clearance for locally advanced Primary and Recurrent Rectal Cancer: A Systematic Review to assess Perioperative Mortality, Rate of R0 Resection and 5Year Overall Mortality. (9th August 2022) - Khan, Rehan; Selvasekar, Chelliah; Jamshed, Nayer; Sahu, Ankit
Abstract: Introduction: The outcomes of complex surgical procedures such as Total pelvic clearance (TPC) have improved due to advances in technology, improvements in surgical technique and experience. Majority of Reviews include older studies diluting the benefits and outcomes. Secondly, very few studies mention all important outcomes in one leading to non-uniformity in reporting of data. Lastly, there was further need of updating the previous reviews, the last one published a decade earlier, hence, the review of Perioperative Mortality, rates of R0 resection and 5-year overall survival were carried out in patients undergoing TPC for primary or recurrent rectal cancer in a systematic manner. Methods: Literature searches were performed in three databases: MEDLINE, PUBMED and Cochrane Library. Each study was evaluated with regards to its design and statistical methodology. The quality assessment of studies was carried out in this review as per the SIGN grading system. Publication bias was assessed by drawing funnel plots for each outcome. Each outcome was further analysed by creating Forrest plot using fixed effect model. Results: A total of 1632 articles were identified through electronic databases. A total of 21 articles were finally included which met the inclusion and exclusion criteria. Out of 963 resections carried out, perioperative mortality was 3.4%. Overall R0 rection rates were 72.4%. Out of total 374 patients, overall, 5-year survival rate was 42%. Conclusion: TPC is safe in experienced hands at specialist centres experienced in dealing with such cases with acceptable outcomes outlined above.